Is 'good' communication achievable in jury instructions? Applying communication theory to instances of instructions in jury trials. - Anesa, Patrizia (Language at Work - Bridging Theory and Practice, 2007)
Stating that 'good' communication plays a crucial role in everybody's personal and professional life would be to state the obvious. However, this well-established concept constantly seems to call for a reflection upon basic questions, such as: how can we define 'good' communication? What are the criteria that can be applied in order to identify it and to discern it, if possible, from 'bad' communication? Is it possible to achieve it? How? Between whom? In which circumstances? What are its consequences?